2004
DOI: 10.1080/13547500400018570
|View full text |Cite
|
Sign up to set email alerts
|

Phenylacetylglycine, a putative biomarker of phospholipidosis: Its origins and relevance to phospholipid accumulation using amiodarone treated rats as a model

Abstract: Amiodarone was given to male Sprague-Dawley rats at a dose of 150 mg kg(-1) day(-1) for 7 consecutive days to induce phospholipidosis in the lungs of treated rats. Amiodarone was given alone or concurrently with phenobarbitone. Animals given amiodarone had raised total phospholipid in serum, lung and lymphocytes, and elevated lyso(bis)phosphatidic acid (LBPA) in all tissues. Urinary and plasma phenylacetylglycine (PAG) and hepatic portal:aortal phenylacetate (PA) ratio were increased, whereas hepatic phenylala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 38 publications
2
46
2
Order By: Relevance
“…Ion images can include other endogenous molecules corresponding to the PhC mass. Additional assessments with model compounds related to species differences of DIPL and drug metabolism, other than amiodarone, may be needed to identify human-or mouse-specific biomarkers including phospholipids through IMS, although phenylacetylglycine and di-docosahexaenoyl-bis(monoacylglycerol) phosphate are biomarkers induced by amiodarone (Delaney et al, 2004;Mesens et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ion images can include other endogenous molecules corresponding to the PhC mass. Additional assessments with model compounds related to species differences of DIPL and drug metabolism, other than amiodarone, may be needed to identify human-or mouse-specific biomarkers including phospholipids through IMS, although phenylacetylglycine and di-docosahexaenoyl-bis(monoacylglycerol) phosphate are biomarkers induced by amiodarone (Delaney et al, 2004;Mesens et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We used chimeric mice (male, 11 to 12-week old) with the middle replacement index (RI) of human hepatocytes (60.8-65.4%), in which the occupancy ratio of the human hepatic region to the total area was estimated based on the human albumin concentration in the blood. Sirajudeen et al (2002) and Delaney et al (2004) reported that total serum and liver phospholipid levels increase after repeated oral administration of 150 and 175 mg/kg amiodarone for 7 and 14 days in rats, respectively. Lipid accumulation was histologically observed in mouse livers administered with 40 mg/kg oral amiodarone for 4 days (Vitins et al, 2014).…”
Section: Animalsmentioning
confidence: 99%
“…Therefore, the increase of TMAO in the serum samples from the AP and medication groups was induced by the digestion of pancreatic tissue. Hippuric acid and PAG are usually produced by intestinal bacteria (Delaney et al, 2004;Phipps et al, 1998), and PAG is the end product of phenylalanine in rodents (James et al, 1972). The increase in the levels of hippuric acid and PAG in the AP groups indicated intestinal bacteria entering the blood, whereas the remaining hippuric acid in the medication groups indicated inhibition by rheum.…”
Section: Other Metabolitesmentioning
confidence: 99%
“…uPAG has also been shown to be affected by parasitic infection [GarciaPerez et al 2010] and dietary intake [O'Sullivan et al 2011]. Several subsequent studies of urinary metabolites in rats with PLD induced by amiodarone reported increases in uPAG [Delaney et al 2004;Dieterle et al 2006;Hasegawa et al 2007]. PAG has therefore been suggested as a surrogate marker for PLD.…”
Section: Introductionmentioning
confidence: 99%
“…PAG is published as a marker for phospholipidosis [Garcia-Perez et al 2010;Espina et al 2001;Robertson et al 2010] even after single compound administration [Nicholls et al 2000;Delaney et al 2004;Hasegawa et al 2007], but the predictivity as a marker is critically discussed within the expert field and it has not been linked to mitochondrial toxicity. In a model tested to detect phospholipidosis with metabonomics techniques after single compound administration using 20 non-phospholipidogenic and 17 phospholipidogenic compounds, Lienemann and colleagues concluded that the induction of phospholipidosis by the test compounds could not be predicted using NMR-based urine analysis or the previously published biomarker PAG [Lienemann et al 2008].…”
Section: Pag As a Biomarker For Phospholipidosis In Association With mentioning
confidence: 99%